Literasi Pasar Modal bagi Siswa SMP melalui Edukasi Investasi Dasar untuk Mendukung Kesadaran Finansial - Tri Utami; May Cahya Rizki; Ulfah Fitriyati; Winda Siti Rukmanah; Fery Citra Febriyanto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Financial literacy has become an essential competency for young people in managing personal finances and making informed financial decisions. However, knowledge of capital market investment among junior high school students remains limited, resulting in low awareness of financial planning and investment opportunities. Therefore, community service activities were conducted to introduce basic investment concepts and improve students’ understanding of the capital market from an early age. This program aimed to enhance financial awareness and provide fundamental knowledge of capital market investment for junior high school students. The Community Service Program (PKM) was carried out at Aruna Surya Bestari Foundation, Pamulang, South Tangerang, on May 14, 2026. The activity was implemented by a team of five lecturers and students from Universitas Pamulang and involved 17 foster children studying at the junior high school level. The program was conducted through several stages, namely preparation, implementation, and reporting. During the implementation stage, participants received educational materials through lectures, practical exercises, discussions, and question-and-answer sessions. The results of the activity indicated an improvement in participants’ understanding of basic investment concepts, capital market instruments, and the importance of financial planning. Participants showed high enthusiasm and active involvement throughout the program. The activity successfully increased students’ financial awareness and encouraged a positive attitude toward responsible financial management and future investment planning.